2019
DOI: 10.13057/biodiv/d200928
|View full text |Cite
|
Sign up to set email alerts
|

Daily activity and diet of Talaud bear cuscus (Ailurops melanotis Thomas, 1898) on Salibabu Island, North Sulawesi, Indonesia

Abstract: Abstract. Authors. 2019. Daily activity and diet of Talaud bear cuscus (Ailurops melanotis Thomas, 1898) on Salibabu Island, North Sulawesi, Indonesia. Biodiversitas 20: 2636-2644. Talaud bear cuscus (Ailurops melanotis) is an endemic species in the Sangihe and Talaud Islands, North Sulawesi, Indonesia. This species is critically endangered in the IUCN Redlist, with a declining population trend. As a protected species in Indonesia, there has not been any specific research on this species. This research aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
4
3
0
Order By: Relevance
“…The high dominance of Canarium asperum explains the high encounters of cuscus on this tree; On Salibabu Island, 3 out of 11 encounters were observed, Bukide Island, two out of three encounters, and Nusa Island, two out of four encounters. This is also supported by Repi et al (2019) who reported that C. asperum is one of the species most consumed by A. melanotis on Salibabu Island, apart from M. peltata and C. odorata. Data on tree level and pole level vegetation is very important in describing the habitat of A. melanotis, this is because, as an arboreal marsupial, A. melanotis utilizes higher level vegetation structure to move and rest, and is highly dependent on forest vegetation density (Repi et al 2019).…”
Section: Vegetationsupporting
confidence: 73%
See 4 more Smart Citations
“…The high dominance of Canarium asperum explains the high encounters of cuscus on this tree; On Salibabu Island, 3 out of 11 encounters were observed, Bukide Island, two out of three encounters, and Nusa Island, two out of four encounters. This is also supported by Repi et al (2019) who reported that C. asperum is one of the species most consumed by A. melanotis on Salibabu Island, apart from M. peltata and C. odorata. Data on tree level and pole level vegetation is very important in describing the habitat of A. melanotis, this is because, as an arboreal marsupial, A. melanotis utilizes higher level vegetation structure to move and rest, and is highly dependent on forest vegetation density (Repi et al 2019).…”
Section: Vegetationsupporting
confidence: 73%
“…This is also supported by Repi et al (2019) who reported that C. asperum is one of the species most consumed by A. melanotis on Salibabu Island, apart from M. peltata and C. odorata. Data on tree level and pole level vegetation is very important in describing the habitat of A. melanotis, this is because, as an arboreal marsupial, A. melanotis utilizes higher level vegetation structure to move and rest, and is highly dependent on forest vegetation density (Repi et al 2019). This is also supported by Riley (2002) who stated that A. melanotis is highly dependent on primary forest.…”
Section: Vegetationsupporting
confidence: 73%
See 3 more Smart Citations